2021
DOI: 10.3389/fnbeh.2021.726218
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Conditioning: What Is Learnt and How it Is Expressed

Abstract: Pairing a neutral conditioned stimulus (CS) with a motivationally significant unconditioned stimulus (US) results in the CS coming to elicit conditioned responses (CRs). The widespread significance and translational value of Pavlovian conditioning are increased by the fact that pairing two neutral CSs (A and X) enables conditioning with X to affect behavior to A. There are two traditional informal accounts of such higher-order conditioning, which build on more formal associative analyses of Pavlovian condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 86 publications
(130 reference statements)
0
15
0
Order By: Relevance
“…In fact, the impact of associatively activated representations on performance has been formally implemented in a recent application of a model of Pavlovian learning and performance (HeiDI; Honey et al, 2020) to higher-order conditioning (Honey & Dwyer, 2021, 2022. The supplementary finding reported by Recio et al (2018)-that placing a distractor between successive presentations of the compounds AX and BX (group Alternating) or AX and AX (and BX and BX; group Blocked) reduced the difference between the groups-might have reflected a disruption to the formation of a (direct) association between A and B in group Alternating, rather than to a process of perceptual learning (see cf.…”
mentioning
confidence: 99%
“…In fact, the impact of associatively activated representations on performance has been formally implemented in a recent application of a model of Pavlovian learning and performance (HeiDI; Honey et al, 2020) to higher-order conditioning (Honey & Dwyer, 2021, 2022. The supplementary finding reported by Recio et al (2018)-that placing a distractor between successive presentations of the compounds AX and BX (group Alternating) or AX and AX (and BX and BX; group Blocked) reduced the difference between the groups-might have reflected a disruption to the formation of a (direct) association between A and B in group Alternating, rather than to a process of perceptual learning (see cf.…”
mentioning
confidence: 99%
“…These associations had already been implicated in phenomena that appeared to be beyond the scope of the Rescorla-Wagner model (e.g., potentiation : Durlach & Rescorla, 1980; unblocking : Rescorla & Colwill, 1983). Moreover, there is a significant body of independent evidence demonstrating their ubiquity, from studies of sensory preconditioning (e.g., Brogden, 1939; Rescorla, 1980; Rescorla & Cunningham, 1978) and second-order conditioning (e.g., Pavlov, 1927; Rescorla, 1982; Rizley & Rescorla, 1972; for a recent review, see Honey & Dwyer, in press, 2021). Indeed, recent evidence has revealed that such within-compound (or sensory) associations exhibit fundamental similarities to Pavlovian conditioning (e.g., Maes et al, 2020).…”
Section: Associative Change Of Stimuli Conditioned In Compoundmentioning
confidence: 99%
“…Equations 1 and 2 illustrate this rule in the context of Pavlovian conditioning trials, with the general form of the rule for any two stimuli (1 and 2) being: ΔV 1-2 = α 1 (c.α 2 − ∑V TOTAL-2 ). The consistent application of the rules generates associative chains (e.g., CS1→CS2→US), which can also contribute to performance (see Honey & Dwyer, in press, 2021).…”
Section: Heidi Simulationsmentioning
confidence: 99%
See 2 more Smart Citations